Manufacturing of sheet metal components with variants using process adapted semi-finished products - Merklein, Marion; Plettke, Raoul; Schneider, Thomas; Opel, Simon; Vipavc, Daniel (Key Engineering Materials, 2012)
Functional sheet metal components can be manufactured through the use of bulk forming operations on sheet metal semi-finished parts. Challenging are the high forming forces and the exact control of material flow. The manufacturing of the semi-finished parts with a defined sheet thickness characteristic occurs on the basis of the processes upsetting and orbital forming. Following a forming operation is presented for the production of an external geared component. The potential for the enhancement of the process limits by use of tailored blanks is demonstrated.© (2012) Trans Tech Publications.
LFT Import::2019-07-29 (1783)
Keywords: Deep-drawing; FE-simulation; Orbital forming; Sheet-bulk metal forming; Upsetting